The feasibility of using the Körperkoordinationstest fur Kinder (KTK) in a U.S. elementary physical education setting to assess gross motor skills specific to postural balance - Campbell-Pierre, Daryl; Rhea, Deborah J. (Frontiers in Sports and Active Living, 2023)
For the past ten years, falls have been the leading cause of nonfatal injuries for all age groups less than 15 years old. A significant rise in childhood sedentary behavior in schools and limited opportunities to be outside has led to motor coordination deficits which have contributed to fall injuries. There is a German assessment tool called the Körperkoordinationstest fur Kinder (KTK), which has been used for decades in Western European countries that allows researchers and physical education teachers to evaluate typical and atypical children's motor coordination competencies related to dynamic postural balance successfully. There is no research published on the use of this assessment tool in the United States but would close a gap in determining these motor coordination deficits in typical and atypical children if found to be feasible in this country. Therefore, this study was divided into two phases. Phase 1 was to determine the feasibility of using the KTK assessment to evaluate gross motor coordination skills specific to postural balance in American children. Phase II was to determine the adaptability of the scoring protocol from use in other countries to the United States. Raw scores and motor quotient scores were compared between 8–10-year U.S. children who were assessed in physical education classes in this feasibility study with 8–10-year-old Flemish children from the 2008 suitability study. The Phase 1 results revealed the KTK assessment was deemed feasible to administer in an American physical education class by addressing three glaring challenges to administering the KTK assessment, which is the KTK implementation focuses, time to assess each skill, and the equipment availability and cost to implement the test in a physical education setting. The Phase II results revealed that American children’s KTK motor coordination ability levels could be identified by implementing the KTK feasibility strategies addressed in Phase 1.